Kebijakan Hukum Pidana dalam Penanggulangan Penyalahgunaan Narkotika - Intan Nur'Aini; Anindya Intan Pandini; Herfita Ayu Nayla; Nanda Patmawati (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The abuse of narcotics and psychotropic substances has become increasingly widespread in Indonesia. These two dangerous substances can damage the morals of the younger generation, which is why the Indonesian government enacted Law No. 35 of 2009 concerning Narcotics and Psychotropic Substances. With the implementation of this regulation, it is expected that illegal drug use will be reduced. The form of research we used is qualitative, by collecting data from various sources and conducting. The results of our study show that illegal narcotics use in Central Java remains relatively high, especially in the city of Semarang. This is due to factors such as free social interaction and the influence of Western culture. This issue needs to be addressed by the authorities, such as the Central Java National Narcotics Agency (BNN) and the Central Java Regional Police. Our research also found several cases of narcotics abuse in Magelang. The government and law enforcement officials must strengthen rehabilitative approaches for drug users so that they are not solely subjected to criminal penalties, but are also given sanctions through medical and social rehabilitation processes.